Think-Pair-Share strategy using smartphone to assist in-class formative assessment / Syahrul Afzal Che Abdullah ... [et al.] - Che Abdullah, Syahrul Afzal; Adam, Basyir; Che Soh, Zainal Hisham; Kamaru Zaman, Fadhlan Hafizhelmi; Sheikh Rahimullah, Bibi Norashiqin; Abidin, Ahmad Farid (UiTM Press, 2018)
Think-Pair-Share strategy is a cooperative learning technique that encourages individual participation through questions. Recent study indicated that a fair number of students chose not to participate in this learning activity. To address this issue, in-class measurement and assessment of student understanding has been developed. Based on a client-server model, the Student Response System (SRS) adopted the think-pair-share strategy using students’ smartphone as clients. Three distinct levels of answering the questions were asked; i.e. in the think phase, students independently develop their own ideas on the specific topic that has been asked, while in the pair stage, students discuss their view with a partner that allow students to express their thoughts and ideas while considering those of their partner, and finally, in the share phase, students share their refined ideas with a larger group such as the whole class with the support of their partner. On the server side, responses from students on questions posed can be automatically viewed by instructor during the Teaching and Learning process. Initial result is encouraging, i.e. experiment with a group of students has managed to improve assessment of their understanding up to seventy percent, while helping to improve students’ socialization processes through interactions among students while strengthening their cognitive and affective domain.